Influence of water stress on the chemical composition of seeds of two Lupins (Lupinus albus and Lupinus mutabilis) - Carvalho, Isabel Saraiva de (2012)
We have performed chemical proximate analysis and determined the carbohydrate profile of mature seeds of Lupinus albus, cv. Rio Maior and Lupinus mutabilis, cv. Potosi plants, either well watered (ww) or subjected to a water-stress period (imposed from the 15th to 35th day after anthesis). Protein content from lupin seeds was 450 and 320 g kg−1 of seed on dry weight basis, for ww plants, respectively, of L. albus and L. mutabilis. Water stress did not affect protein content. The oil content of ww plants was about 120 g kg−1 of seed dry weight for L. albus and 180 g kg−1 of seed dry weight for L. mutabilis. Water stress reduced those values of half. The sugar content was about 90 g kg−1 for L. albus and 50 g kg−1 of seed dry weight for L. mutabilis, in ww plants. Water stress led to an increase in sugar content to 200 and 130 g kg−1 of seed dry weight, respectively, for L. albus and L. mutabilis. The α-galactosides amounted to 70 % of the total sugars (raffinose being 30 % and stachyose, 40 %) and sucrose was about 20 % of the total sugars. Water stress increased total carbohydrates and increased the sucrose/α-galactoside ratio, although reducing raffinose content and increasing sucrose content.